Entrepreneurship Education Management A Site Study At SMK Muhammadiyah 1 Blora - Sutristriyanti, Nunuk; , Prof. Dr. Yetty Sardjono, M.Si; , Dr. Phil. Dewi Candraningrum, M.Ed (2013)
This Study entitled Entrepreneurship Education management: A site study at SMK Muhammadiyah 1 Blora has expected goals: 1) to describe the learning implementation of entrepreneurship, 2) to identify the learning mplementation of Entrepreneurship, 3) to describe the learning evaluation of Entrepreneurship at SMK Muhammadiyah 1 Blora, in 2012/2013 year academic. The approach used in this research was ethnography qualitative. The methods to colleat the data included observation, interviews, and documentation. Validity of the data obtained with the persistence of observation, triangulation, and examination peers through discussion, and detailed description. Techniques in an interactive data analysis through the collection process reducing, presenting, and draw conclusions. The result of this research can be concluded that Entrepreneurship learning in SMK Muhammadiyah 1 Blora by using learning plan arranged systematically. Learning plan consists of syllabus and lesson Plan (RPP). The syllabus is arranged by team entrepreneurship teacher at school before the new school year, while lesson plan is arranged by each Entrepreneurship teacher which include the material given and based on the condition of school . The Learning implementation is based on lesson plan that is made by teacher. Learning the process was done by giving and developing Entrepreneurship. It consists of systematically learning, active, creative, effective, interactive, and communicative, so we can get the values from student learning entrepreneurship easily, student feel thing appreciated, interested, trained to solve problem, try to give ideas, and develop ability that they have.The Learning evaluation includs cognitive, affective, and psychomotoric during and after the learning process.